Soluble guanylate cyclase activator BAY 54–6544 improves vasomotor function and survival in an accelerated ageing mouse model. Issue 9 (27th August 2022) - Ataei Ataabadi, Ehsan; Golshiri, Keivan; Jüttner, Annika A.; de Vries, René; Van den Berg‐Garrelds, Ingrid; Nagtzaam, Nicole M. A.; Khan, Hina N.; Leijten, Frank P. J.; Brandt, Renata M. C.; Dik, Willem A.; van der Pluijm, Ingrid; Danser, A. H. Jan; et al.
Abstract: DNA damage is a causative factor in ageing of the vasculature and other organs. One of the most important vascular ageing features is reduced nitric oxide (NO)soluble guanylate cyclase (sGC)—cyclic guanosine monophosphate (cGMP) signaling. We hypothesized that the restoration of NO‐sGC‐cGMP signaling with an sGC activator (BAY 54–6544) may have beneficial effects on vascular ageing and premature death in DNA repair‐defective mice undergoing accelerated ageing. Eight weeks of treatment with a non‐pressor dosage of BAY 54–6544 restored the decreased in vivo microvascular cutaneous perfusion in progeroid Ercc1 ∆/− mice to the level of wild‐type mice. In addition, BAY 54–6544 increased survival of Ercc1 ∆/− mice. In isolated Ercc1 ∆/− aorta, the decreased endothelium‐independent vasodilation was restored after chronic BAY 54–6544 treatment. Senescence markers p16 and p21, and markers of inflammation, including Ccl2, Il6 in aorta and liver, and circulating IL‐6 and TNF‐α were increased in Ercc1 ∆/−, which was lowered by the treatment. Expression of antioxidant genes, including Cyb5r3 and Nqo1, was favorably changed by chronic BAY 54–6544 treatment. In summary, BAY 54–6544 treatment improved the vascular function and survival rates in mice with accelerated ageing, which may have implication in prolonging health span in progeria and normal ageing. Abstract : DNA repair deficiency in Ercc1∆/− mice cause a disruption of NO‐sGC‐cGMP signaling and a decrease of vasodilator response. These mice die prematurely between the age of 14 and 26 weeks and can be used to test interventions in ageing. Treatment with the BAY 54–6544 improved NO‐mediated vasodilation and attenuated vascular senescence and inflammation markers. Moreover, these changes are not restricted to vascular tissue, but manifest themselves also in liver, an organ that is often used to study changes in common ageing pathways in various models. Thus, BAY 54–6544 could be a potential therapeutic treatment to attenuate vascular ageing and improve survival.